The impact of regionalism on the multilateral trading order: French tariff bargaining in the Uruguay Round - Daniel Piazolo (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
This paper analyzes the GATT negotiations during the Uruguay Round and shows that France was induced to accept a more free trade oriented package due to her integration into the European community. The importance of the European economic and diplomatic relationships led France to accept a GATT deal which she felt would be disadvantageous. Further, the paper investigates how this finding fits into the literature of the political economy of trade policy and how it can be incorporated into a game theoretic model of endogenous tariff making.
Keywords: C78; F13; F15; 330; Regionalism; Uruguay Round; European Union; Tariffs; Bargaining Model; Agrarzoll; Außenhandelsliberalisierung; Verhandlungen; Public Choice; Frankreich; Deutschland; USA